Numerical Study for Quantitative Assessment of Ground Displacements of Rock-Mass Slopes under Static and Seismic Conditions in the Landfall Areas of Offshore Pipelines - Σταυρουλάκης, Εμμανουήλ (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2018)
Ιn the last decades, environmental considerations in coastal and offshore zones have shown a remarkable increase. In this sense, the integrity of coastal facilities, offshore oil & gas installations and facilities, and various pipeline networks both offshore and onshore play an important role due to their significant economic feasibility and environmental sustainability.